The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-73605/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Noninvasive Model to Predict Liver Histology for Antiviral Therapy Decision in Chronic Hepatitis B with Alanine Aminotransferase<2 Upper Limit of Normal

Abstract: Background and Aim: Although liver biopsy is currently the gold standard to evaluate liver histology, it has many limitations, such as sampling error, cost and risk of complications. This study aims to construct a noninvasive model to predict liver histology for antiviral therapy in chronic hepatitis B (CHB) with alanine aminotransferase (ALT)<2 times upper limit of normal(ULN).Methods: We retrospectively analyzed 577 patients with CHB who received liver biopsy and whose ALT was less than 2 ULN. Then they were… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A noninvasive [29]. AGH model composed of AST, hepatitis B core antigen and GGT is a reliable index to predict moderate to severe inflammation or significant fibrosis, which helps to determine the initiation of antiviral therapy [30]. But the predictive value of our model is better than AGH model.…”
Section: Discussionmentioning
confidence: 85%
“…A noninvasive [29]. AGH model composed of AST, hepatitis B core antigen and GGT is a reliable index to predict moderate to severe inflammation or significant fibrosis, which helps to determine the initiation of antiviral therapy [30]. But the predictive value of our model is better than AGH model.…”
Section: Discussionmentioning
confidence: 85%
“…Following publication of the original article [ 1 ], the authors identified incorrect corresponding author mentioned. Correct corresponding author is Haijun Huang.…”
Section: Correction To: Bmc Gastroenterol (2021) 21:4 Httpsmentioning
confidence: 99%